A guerra no contestado em defesa de um modo de vida : análise da construção dos laços sociais entre os caboclos (1912-1916) - Rocha, Milliann Carla Strona De Godoy (2020)
This research aims to investigate, in a critical way, what united men and women from different social contexts to resist the attack of the armed forces of the Brazilian State during the Contestado War (1912-1916). The aim is to analyze how the social ties between the caboclos were built during the war, and how the networks of sociability were used by the leaders in this process. From the study of social relations historically built, it is intended to observe the connection of these subjects with the territory and the criminalization of the movement from the point of view of the local elites. This research starts from the hypothesis that there is an aggregative force around the networks of sociability of the caboclos that was used to keep the group at war in the face of so many difficulties. The theoretical and methodological support will be Micro-History, thus, the municipality of Curitibanos, in Santa Catarina, between 1912 and 1916, was selected as a chronological and spatial point of view. The sources used will be criminal cases from the Curitibanos region, Messages and Official Reports from the Government of the States of Paraná and Santa Catarina. The analytical and indicative method will be used to examine the sources. This research seeks to contribute with relevant reflections on the criminalization of the movement, as well as to point out new perspectives on the Studies of Contestado, demonstrating the relevance of this peasant struggle in the Latin American context considering the conflict in the context of the twentieth century in Brazil, which was marked by ideas of modernization and policies to encourage Migration, as foreign capital and migration were factors that contributed to alter the local way of life of the caboclos, thus modifying their relations with the territory.